Bioinspired Superhydrophobic Surfaces via Laser-Structuring - Liu, Monan; Li, Mu-Tian; Xu, Shuai; Yang, Han; Sun, Hong-Bo (Frontiers in Chemistry, 2020)
Bioinspired superhydrophobic surfaces are an artificial functional surface that mainly extracts morphological designs from natural organisms. In both laboratory research and industry, there is a need to develop ways of giving large-area surfaces water repellence. Currently, surface modification methods are subject to many challenging requirements such as a need for chemical-free treatment or high surface roughness. Laser micro-nanofabrications are a potential way of addressing these challenges, as they involve non-contact processing and outstanding patterning ability. This review briefly discusses multiple laser patterning methods, which could be used for surface structuring toward creating superhydrophobic surfaces.